Improved hydrogenation function of Pt@SOD incorporated inside sulfided NiMo hydrocracking catalyst. Issue 6 (4th November 2015) - Sibi, M. G.; Rai, Aditya; Anand, Mohit; Farooqui, Saleem A.; Sinha, A. K.
Abstract : A multifunctional catalyst with Pt incorporated inside sodalite cages (SOD) encapsulated in ZSM-5 supported with Ni and Mo was synthesized, characterized and evaluated as a hydrocracking catalyst for the conversion of triglycerides to kerosene and diesel. Abstract : A multifunctional catalyst with Pt incorporated inside sodalite cages (SOD) encapsulated in ZSM-5 supported with Ni and Mo was synthesized, characterized and evaluated as a hydrocracking catalyst for the conversion of triglycerides to kerosene and diesel. The Pt@SOD was further encapsulated inside hierarchical mesoporous ZSM-5 zeolite to prepare a bifunctional catalyst (H-ZSM-5 for acid functionality and sulfided NiMo along with Pt@SOD for hydrogenation functionality). Metal dispersion, temperature programmed reduction (TPR, H2 ) and temperature programmed desorption (TPD, ammonia) studies were done to evaluate the bifunctional nature of the catalyst. The sulfided NiMo-Pt@SOD-ZSM-5 catalyst showed improved catalytic activity compared to the sulfided NiMo-ZSM-5 catalyst under severe reaction conditions of low hydrogen/feed ratio. We show for the first time that it is possible to operate at low H2 concentrations during hydroprocessing of triglycerides with 99% conversion and 93% selectivity for diesel range compounds at 250 NL L −1 and 380 °C temperature. Computational studies showed that H2 molecules activated by Pt inside the sodalite cages are available for reactions outside the cages. The synthesized catalyst showed high hydrodeoxygenation activity even at lower pressure (50–60 bar) and hydrogen/feed ratios of 500–1500 NL L −1 . The catalyst showed better stability against deactivation (4 times less coke deposition) than sulfided NiMo-ZSM-5 catalyst during a continuous run due to the presence of Pt@SOD.